Spontaneous neurotransmission: An independent pathway for neuronal signaling? - Kavalali, Ege (2011)
Recent findings suggest that spontaneous neurotransmission is a bona fide pathway for interneuronal signaling that operates independent of evoked transmission via distinct presynaptic as well as postsynaptic substrates. This article will examine the role of spontaneous release events in neuronal signaling by focusing on aspects that distinguish this process from evoked neurotransmission, and evaluate the mechanisms that may underlie this segregation.